THE ANALYSIS OF ITEM PROBLEMS IN HIGH SCHOOL MATHEMATICS TEXTBOOK IN INDONESIA (2016 REVISION EDITION) REVIEWED FROM THE COGNITIVE ASPECT OF TIMSS - Khodaria, Siti; Maharani, Anggita; Sulaiman, H (Universitas Kuningan, 2019)
This study aims to analyze the question items on two supplementary Indonesian mathematics textbooks (revised edition 2016) of 2013 curriculum for XI graders and compare the analysis using 2015 TIMSS assessment framework. This study apply qualitative study with naturalistic approach. The analysis results consist of 104 question items and 85 items of practice test. On a book published by PT. SEWU Bandung shows 3.5% of knowing cognitive domain, 4.71% applying, and 91.76% reasoning. The analysis on 19 items of practice test on a book is published by PT. Bumi Aksara Jakarta. It shows 10.53% applying, 89.47% reasoning, but not showing a percentage on knowing cognitive domain. Results of the question items analysis on knowing and applying cognitive domain for both the books are less percentage than reasoning cognitive domain. Thus, the results of analysis of two textbooks are not yet in accordance with TIMSS. Nevertheless, the comparison of the analysis on knowing cognitive domain in a book published by PT. SEWU Bandung is close to what have expected by TIMSS. Meanwhile, on applying and reasoning cognitive domain the book published by PT. Bumi Aksara Jakarta is close to what have expected by TIMSS.